2020
DOI: 10.1021/acsmaterialslett.0c00240
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Polymers with Nitrogen-Containing Tripodal Crosslinkers for Efficient PFAS Adsorption

Abstract: Per-and polyfluoroalkyl substances (PFAS) are widely used industrial chemicals that are of a great concern because of their pervasive presence in water resources and association with negative health effects. Crosslinked β-cyclodextrin-containing (β-CD) polymer adsorbents have shown promising performances for sequestering PFAS. Recently, installing amino groups into the crosslinkers of a β-CD polymer network improved the binding of many anionic PFAS, including short-chain and branched derivatives. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 28 publications
5
73
0
Order By: Relevance
“…They found that the CDP1 with amino groups outperformed the amidefunctionalized polymer CDP2 with amido groups for the removal testing of 10 anionic PFAS (C4-C10). It was confirmed that the high loading of amino groups in CDP1 was mainly responsible for the superior removal PFAS performance, while amido groups in CDP2 cannot be protonated, underscoring the importance of electrostatic interactions to sequester PFAS (Yang et al, 2020). As the result, CDP1 exhibited the highest affinity and adsorption capacity among CD-based sorbents for GenX (222 mg/g) and PFOA (457 mg/g).…”
Section: Cyclodextrinsmentioning
confidence: 80%
See 2 more Smart Citations
“…They found that the CDP1 with amino groups outperformed the amidefunctionalized polymer CDP2 with amido groups for the removal testing of 10 anionic PFAS (C4-C10). It was confirmed that the high loading of amino groups in CDP1 was mainly responsible for the superior removal PFAS performance, while amido groups in CDP2 cannot be protonated, underscoring the importance of electrostatic interactions to sequester PFAS (Yang et al, 2020). As the result, CDP1 exhibited the highest affinity and adsorption capacity among CD-based sorbents for GenX (222 mg/g) and PFOA (457 mg/g).…”
Section: Cyclodextrinsmentioning
confidence: 80%
“…With this reduced polymer, anionic PFAS with C4-C10 were indiscriminately removed at high efficiency (80%-95% after 30 min), which outperformed GAC and PAC, especially for short-chain PFAS (PFBA removal >80%, while GAC and PAC have the removal of 40%-50%) (Klemes et al, 2019). To better understand the effect of the amino groups on the interactions between β-CD polymer and anionic PFAS, Yang et al (2020) selected two different tripodal crosslinkers containing amino or amido groups, respectively. They found that the CDP1 with amino groups outperformed the amidefunctionalized polymer CDP2 with amido groups for the removal testing of 10 anionic PFAS (C4-C10).…”
Section: Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, Yang et al compared different β-CD polymers. The results demonstrated that the affinity of the polymers containing amine groups for removal of anionic PFAS was higher than that of amido polymers [ 83 ].…”
Section: Applications Of Cyclodextrin-based Materials and Polymers In Food Sciencementioning
confidence: 99%
“…Alternative designs using thin films hosting adsorbent resins have also shown promise (Challis, 2018). New types of PFAS-specific adsorbents, including sol-gel derived media with ionic sites, have demonstrated that adsorption can be tailored (Wang et al, 2017;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%